2022
DOI: 10.1111/eci.13842
|View full text |Cite
|
Sign up to set email alerts
|

Circulation tumour DNA in predicting recurrence and prognosis in operable colorectal cancer patients: A meta‐analysis

Abstract: Background Selecting the appropriate patient for further treatment after surgery and adjuvant chemotherapy (ACT) for colorectal cancer (CRC) can improve the patient's prognosis. Circulating tumour DNA (ctDNA) has the potential to predict recurrence and prognosis after CRC surgery and ACT, but the results are still inconclusive. Objectives As the completed studies have small sample sizes and different experimental methods, a meta‐analysis was conducted to assess the ctDNA on recurrence and prognosis after CRC s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“… 106 The main reason for this result may be postoperative minimal residual cancers and occult metastasis. Previous meta-analyses of single cancer all showed that the presence of ctDNA was associated with cancer recurrence (for CRC, 107 BC, 108 NSCLC, 109 and ESCA, 110 respectively). Our meta-analysis defined the time point as postoperative.…”
Section: Discussionmentioning
confidence: 99%
“… 106 The main reason for this result may be postoperative minimal residual cancers and occult metastasis. Previous meta-analyses of single cancer all showed that the presence of ctDNA was associated with cancer recurrence (for CRC, 107 BC, 108 NSCLC, 109 and ESCA, 110 respectively). Our meta-analysis defined the time point as postoperative.…”
Section: Discussionmentioning
confidence: 99%
“…[9] ctDNA contains complete information on tumor variation and has developed rapidly in recent years for guiding tumor treatment and monitoring treatment outcome and prognosis. [10][11][12] The concentration of ctDNA in the blood is very low…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 ] ctDNA contains complete information on tumor variation and has developed rapidly in recent years for guiding tumor treatment and monitoring treatment outcome and prognosis. [ 10 12 ] The concentration of ctDNA in the blood is very low and accounts for approximately 0.01%–2% of cell-free DNA (cfDNA), where cfDNA is derived from white blood cells and consists of double-stranded DNA fragments of approximately 140 to 170 base pairs (bp) in length and ctDNA usually consists of < 145 bp in length. Moreover, previous biotechnologies had low sensitivity for detecting ctDNA.…”
Section: Introductionmentioning
confidence: 99%